2005
DOI: 10.1046/j.1540-8167.2005.40759.x
|View full text |Cite
|
Sign up to set email alerts
|

How Close Are the Phrenic Nerves to Cardiac Structures? Implications for Cardiac Interventionalists

Abstract: The right phrenic nerve is at risk when ablations are carried out in the superior caval vein and the right superior pulmonary vein. The left phrenic nerve is vulnerable during lead implantation into the great cardiac and left obtuse marginal veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
173
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(177 citation statements)
references
References 28 publications
2
173
0
2
Order By: Relevance
“…An anatomical study investigating 19 human cadavers revealed the close proximity of the right PN to both the superior vena cava (minimum 0.3±0.5 mm) and the right superior PV (minimum 2.1±0.4 mm). 66 The anterior wall of the right superior PV was <2 mm from the right PN in 32% of the specimens. The left PN passed over the obtuse cardiac margin and the left obtuse marginal vein and artery in 79% of the specimens.…”
Section: Pn Injurymentioning
confidence: 89%
“…An anatomical study investigating 19 human cadavers revealed the close proximity of the right PN to both the superior vena cava (minimum 0.3±0.5 mm) and the right superior PV (minimum 2.1±0.4 mm). 66 The anterior wall of the right superior PV was <2 mm from the right PN in 32% of the specimens. The left PN passed over the obtuse cardiac margin and the left obtuse marginal vein and artery in 79% of the specimens.…”
Section: Pn Injurymentioning
confidence: 89%
“…It is thought that the phrenic nerve gets injured due to the close anatomic relationship of the phrenic nerve to the heart (Figure 3). Both the right and the left phrenic nerves can get damaged -the right phrenic nerve is specifically at risk when ablations are carried out in the superior caval vein and the right superior pulmonary vein, and the left phrenic nerve is liable to damage during lead implantation into the great cardiac and left obtuse marginal veins (8). In our patient, the right phrenic nerve, which runs along the lateral surfaces of the superior vena cava and right atrium, was injured by energy delivered to the adjacent area during ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the left phrenic nerve can, along its course, come close to the CGV, so capture of the phrenic nerve by highoutput pacing inside the GCV can likewise prohibit safe ablation in that site. 7 For all of the above reasons, it is not surprising that the reported rate of acute success with ablation of GCV/AIV PVCs is 43% to 70% only. 4,8,9 For the same reasons, it is important to have alternative strategies for ablating such PVCs.…”
Section: Discussionmentioning
confidence: 99%